Tightly-bound to DNA proteins in rat experimental hepatomas and normal liver cells - Labeikyte, D.; Borutinskaite, V.; Legzdins, N.; Sjakste, N. (Experimental Oncology, 2011)
Proteins tightly bound to DNA (TBP) comprise a group of proteins that remain bound to DNA even after harsh deproteinization procedures. The amount of these proteins is 20–100 µg for mg of DNA depending on eukaryotic source. This experimental paper examines the possibility to use some TBP for clinical biomarker discovery, e.g. for identification of prognostic and diagnostic cancer markers. The main aim of this study was to designate differences between tightly DNA binding protein patterns extracted from rat liver and rat experimental hepatomas (Zajdela ascites hepatoma and hepatoma G-27) and to evaluate possibility that some of these proteins may be used as biomarkers for cell cancer transformation. Methods: We used proteomics aproach as a tool for comparison of pattern of TBP from rat experimental hepatomas and normal liver cells. Combination of 2DE fractionation with mass spectrometry (MALDI TOF-MS) suitable for parallel profiling of complex TBP mixtures. Results: Intriguingly 2DE protein maps of TBP from rat liver and rat experimental hepatomas (Zajdela acites hepatoma and hepatoma G-27) were quite different. We identified 9 proteins, some of them shared in all TBP patterns. Among identified tightly bound to DNA proteins there were three proteins considered as nuclear matrix proteins (lamin B1, scaffold attachment factor B1, heterogeneous nuclear ribonucleoprotein). Also we identified DNA repair protein RAD50, coiled-coil domain-containing protein 41, structural maintenance of chromosomes protein1A and some ATP –dependent RNA helicases indicating that TBP are of interest with respect to their potential involvement in the topological organization and/or function of genomic DNA. Conclusions: We suppose that proteomic approach for TBP identification may be promising in development of biomarkers, also obtained results may be valuable for further understanding TBP functions in genome.